Análisis de la sensibilidad de la calidad operacional en sistemas de riego colectivo - Granda Guachizaca, Israel Vinicio. (2015)
Clement formula proposed by the researcher René Clément for calculating circulating flows in a line (pipe) is a method that considers the probability that each hydrant opening within a system during peak or peak period consumption, allows a considerable reduction of diameters. In this context the development of this research where Sensitivity analysis of operational quality systems of collective irrigation, which is applied in calculating flows (Clément) based on probability distributions based on the variation of the collateral is realized poses supply thereby obtaining different scenarios irrigation systems, they are validated by simulation using software where you can get results shall meet the requirements in speed as well as pressures. Verifying concluding with costs based on the pipe obtained scenarios.